How Generative AI Went From Innovation to Risk: Discussions in the Korean Public Sphere - Sunghwan Kim; Jaemin Jung (Media and Communication, 2025)
Technological progress breeds both innovation and potential risks, a duality exemplified by the recent debate over generative artificial intelligence (GAI). This study examines how GAI has become a perceived risk in the Korean public sphere. To explore this, we analyzed news articles (N = 56,468) and public comments (N = 68,393) from early 2023 to mid-2024, a period marked by heightened interest in GAI. Our analysis focused on articles mentioning “generative artificial intelligence.” Using the social amplification of risk framework (Kasperson et al., 1988), we investigated how risks associated with GAI are amplified or attenuated. To identify key topics, we employed the bidirectional encoder representations from transformers model on news content and public comments, revealing distinct media and public agendas. The findings show a clear divergence in risk perception between news media and public discourse. While the media’s amplification of risk was evident, its influence remained largely confined to specific amplification stations. Moreover, the focus of public discussion is expected to shift from AI ethics and regulatory issues to the broader consequences of industrial change.